Twelve-Year Trends of PM10 and Visibility in the Hefei Metropolitan Area of China - Lin Huang; Mindong Chen; Jianlin Hu (Advances in Meteorology)
China has been experiencing severe air pollution and previous studies have mostly focused on megacities and a few hot spot regions. Hefei, the provincial capital city of Anhui province, has a population of near 5 million in its metropolitan area, but its air quality has not been reported in literature. In this study, daily PM10 and visibility data in 2001–2012 were analyzed to investigate the air quality status as well as the twelve-year pollution trends in Hefei. The results reveal that Hefei has been suffering high PM10 pollution and low visibility during the study period. The annual average PM10 concentrations are 2~3 times of the Chinese Ambient Air Quality Standard. PM10 shows fluctuating variation in 2001–2007 and has a slightly decreasing trend after 2008. The annual average visibility range is generally lower than 7 km and shows a worsening trend from 2001 to 2006 followed by an improving trend from 2007 to 2012. Wind speed, precipitation, and relative humidity have negative effects on PM10 concentrations in Hefei, while temperature could positively or negatively affect PM10. The results provide a general understanding of the status and long-term trends of PM10 pollution and visibility in a typical second-tier city in China.